Strategi Kepala Sekolah Dalam Menghadapi Proses Pembelajaran Era Pandemi Di Sekolah Dasar Islam Mohammad Hatta Lowokwaru Malang - Muhammad Ridho (STAI Ma'had Aly Al-Hikam Malang, 2022)
The online learning process is officially regulated by the government through circular letter Number 4 of 2020. The application of online learning has several shortcomings. The unpreparedness of teachers or students in certain areas due to inadequate access, for example, internet network constraints and communication tools. To achieve good learning, school principals determine policies in the pandemic era with proper considerations. This study focuses on revealing the principal's strategy for dealing with the learning process in the pandemic era at Mohammad Hatta Lowokwaru Islamic Elementary School, Malang. This research uses a qualitative approach with the type of case study research. The research instrument is the researcher himself, the auxiliary instruments are observation, interviews, and documentation. The data sources are primary and secondary. The results showed that the principal's strategy in the pandemic era was conducting training for teachers who had difficulty adapting to online learning, supervising teachers during online learning, providing advice, and motivating teachers to learn things related to online learning media. . Supporting factors and inhibiting factors for the principal's strategy in dealing with online learning, complaints and suggestions from teachers and parents of students so that principals can quickly find solutions and adequate facilities so that teachers do not worry anymore. The inhibiting factors were the initial online learning policy for the teachers to be difficult to adapt to and the lack of control from parents